2017
DOI: 10.3389/fpsyg.2017.00707
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Failure in Analogical Reasoning Tasks: A Problem of Focus of Attention and Information Integration?

Abstract: Children’s improved performance with age in analogy tasks has been explained by an increase in semantic knowledge of the items and the relations between them or by the development of an increased ability to inhibit irrelevant information. We tested the so-called “unbalanced attentional focus hypothesis” that claims that a failure to choose the “analogical” match can be the result of a difficulty to focus on all the relevant information available. Previous eye-tracking research has suggested, in analogies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 54 publications
(121 reference statements)
2
38
0
Order By: Relevance
“…It is possible that interventions like these elicit a general increase in children's prioritization of relations (e.g., Walker, Hubachek, & Vendetti, 2018), as Vendetti et al (2014) found with adults. However, none of the prior work with children has shown transfer to new relations on a separate task; thus, these improvements could also have been driven by increasing the quantity, quality, or accessibility of specific relational knowledge representations needed during the task (e.g., Glady, French, & Thibaut, 2017;Loewenstein & Gentner, 2005) or by decreasing the burden placed on cognitive resources while reasoning on the task (e.g., Richland & McDonough, 2010;Thibaut, French, & Vezneva, 2010b).…”
Section: Relational Mindsetmentioning
confidence: 99%
“…It is possible that interventions like these elicit a general increase in children's prioritization of relations (e.g., Walker, Hubachek, & Vendetti, 2018), as Vendetti et al (2014) found with adults. However, none of the prior work with children has shown transfer to new relations on a separate task; thus, these improvements could also have been driven by increasing the quantity, quality, or accessibility of specific relational knowledge representations needed during the task (e.g., Glady, French, & Thibaut, 2017;Loewenstein & Gentner, 2005) or by decreasing the burden placed on cognitive resources while reasoning on the task (e.g., Richland & McDonough, 2010;Thibaut, French, & Vezneva, 2010b).…”
Section: Relational Mindsetmentioning
confidence: 99%
“…Thus, it is vital to understand the mechanism underlying children's analogical reasoning and further support analogical reasoning development. Recently, a large body of literature attempted to intervene the development of analogical reasoning from the perspective of traditional developmental psychology . While the intervention methods in these studies are simple (eg, just changing materials presentation) and the effects cannot maintain (eg, without longitudinal studies to focus the long‐term intervention effect).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggests that children's analogical reasoning accuracy decreases as the number of perceptual or semantical distractors in the task increases . Several eye tracking studies investigated the development of analogical reasoning with classically pictorial A:B::C:D analogical problems .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more systematic investigations of the onset of the illusion are rare. The present study by Yeh and colleagues examines the relationship between executive functions like attention shifts and the experience of the rubber hand illusion, i.e., they investigate the role of top-down processes in the perception of the illusion (Yeh et al, 2017 ). Importantly, the authors use not only questionnaire ratings, but also measure the illusion onset, thus asking the participants when “…they begin to experience the rubber hand as belonging to the self…” (p.4).…”
mentioning
confidence: 99%